2017
DOI: 10.3390/molecules22060937
|View full text |Cite
|
Sign up to set email alerts
|

Levo-Corydalmine Alleviates Neuropathic Cancer Pain Induced by Tumor Compression via the CCL2/CCR2 Pathway

Abstract: Background: Tumor compression-induced pain (TCIP) is a complex pathological cancer pain. Spinal glial cells play a critical role in maintenance of cancer pain by releasing proinflammatory cytokines and chemokines. In this study, we verified the role of levo-corydalmine (l-CDL) on TCIP. Methods: Spontaneous pain, paw withdrawal threshold and latency were assessed using TCIP mouse model. Immunofluorescence was used to identify the reactions of glia. RT-PCR and western blot or ELISA were used to determine mRNA or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Dishes were rinsed with PBS and incubated with goat antirabbit IgG/FITC and goat anti-rabbit IgG/Cy3, respectively for 2 h at room temperature, and the nuclei was stained with DAPI. 16 The stained dishes were examined with laser scanning confocal microscope (Carl Zeiss, Oberkochen, Germany) and images were assessed by Image J 1.50i (National Institutes of Health, USA).…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%
“…Dishes were rinsed with PBS and incubated with goat antirabbit IgG/FITC and goat anti-rabbit IgG/Cy3, respectively for 2 h at room temperature, and the nuclei was stained with DAPI. 16 The stained dishes were examined with laser scanning confocal microscope (Carl Zeiss, Oberkochen, Germany) and images were assessed by Image J 1.50i (National Institutes of Health, USA).…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%
“…In the current study, the natural compound l -CDL, which exerted a potent analgesic effect on alleviating bone cancer pain, significantly attenuated morphine tolerance by antagonizing spinal D2DR at nonnarcotic analgesic doses, and we further explored its underlying mechanism. Both intragastric and intrathecal administration of l- CDL were reported to attenuate chronic pain, 19 , 46 , 47 and l- CDL (p.o.) did not affect the motor function of rats 19 at analgesic doses in our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…l -CDL is an alkaloid from the traditional Chinese Medicine, Corydalis yanhusuo W. T. Wang, and is also the main metabolite of l -tetrahydropalmatine ( l- THP), which possesses analgesic effects and has been used as an analgesic and sedative medicine for more than 40 years in China. In our previous report, we discovered that l- CDL reduced cancer-induced and vincristine-induced neuropathic pain and chronic bone cancer pain in the spinal cord 14–16. Additionally, previous studies have demonstrated that l -CDL inhibited the activation of spinal neurons, astrocytes, and microglia in patients with neuropathic cancer pain and vincristine-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 92%